Enhancing Purchase Decisions for Cimory Yoghurt through Price Perception and Product Quality - Nur Asy Syifa Priantna; Riezky Bagus Prawira Darwadi; Nurbaiti Nurbaiti; Siti Aisyah (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to examine the influence of price perception and product quality on purchasing decisions of Cimory Yoghurt among the people of Medan city. The research employed a quantitative approach using questionnaires for data collection. The sample comprised 100 respondents selected through purposive sampling. The findings revealed that price perception had a negative and insignificant effect on purchasing decisions, suggesting that price is not the primary factor influencing consumer buying behavior. In contrast, product quality had a positive and significant impact, indicating that higher perceived quality leads to a higher likelihood of purchasing Cimory Yoghurt. These results offer practical implications for Cimory's management, underscoring the importance of maintaining and enhancing product quality to attract consumer interest, rather than focusing solely on pricing strategies. The study contributes to a deeper understanding of consumer behavior in the yogurt market in Medan.